Establishing an investigational drugs and research residency at an academic medical center. (13th September 2019) - Wascher, Molly; Mighty, Janet; Brown, Victoria; Ashby, Daniel; Rudek, Michelle A; Nesbit, Todd; DeLisa, Anne; Walker, Cathy; Tolan, Meghan
Abstract: Purpose: The development, structure, and implementation of an innovative residency program designed to help meet a growing need for pharmacists with specialized expertise in investigational drug use and clinical research are described. Summary: Clinical research has become an increasingly complex field, but prior to 2017 there were no U.S. specialty residency training programs focused on pharmacists' role in drug development and the care of patients enrolled in clinical trials. In 2016 Johns Hopkins Hospital (JHH) launched an initiative to develop residency training standards specific to the areas of investigational drug use and clinical research. The residency development process consisted of creation of a residency development committee; a needs assessment, including formation of a diverse panel of internal and external experts to guide identification of key competency areas and development of residency goals and objectives; design of the program's structure, including a framework for required and elective rotations; submission of an application for pre-candidate status to the ASHP Commission on Credentialing; and recruitment efforts. Conclusion: The JHH investigational drugs and research residency, a combined PGY1 and PGY2 program with 5 competency areas, 14 goals, and 49 objectives, was granted pre-candidate status by ASHP in November 2016. The first resident began the program in June 2017.